Multiple evanescent white-dot syndrome – case report - Figurska, Małgorzata; Stachowska, Urszula; Kozera, Milena (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
The aim of the work is to present a case report of multiple evanescent white-dot syndrome in the left eye of 34 years old female. It’s a rare disease entity which runs as a idiopathic inflammation of retina and choroid. Additional investigations which are performed in the clinic such as fluorescein angiography, indocyanine green angiography validated a primary diagnosis in this case. Intravenous infusion of methylprednisolone was administered with oral steroid continuation of therapy during four weeks. A quick visual improvement to 1.0 in the left eye was obtained with removal of characteristic for MEWDS alterations in additional investigations.